Discovery of facile amides-functionalized rhodanine-3-acetic acid derivatives as potential anticancer agents by disrupting microtubule dynamics - Zhou, Xiang; Liu, Jiamin; Meng, Jiao; Fu, Yihong; Wu, Zhibin; Ouyang, Guiping; Wang, Zhenchao (Journal of enzyme inhibition and medicinal chemistry, 2021)
Microtubule dynamics are crucial for multiple cell functions, and cancer cells are particularly sensitive to microtubule-modulating agents. Here, we describe the design and synthesis of a series of (Z)-2-(5-benzylidene-4-oxo-2-thioxothiazolidin-3-yl)-N-phenylacetamide derivatives and evaluation of their microtubule-modulating and anticancer activities in vitro. Proliferation assays identified I 20 as the most potent of the antiproliferative compounds, with 50% inhibitory concentrations ranging from 7.0 to 20.3 µM with A549, PC-3, and HepG2 human cancer cell lines. Compound I 20 also disrupted cancer A549 cell migration in a concentration-dependent manner. Immunofluorescence microscopy, transmission electron microscopy, and tubulin polymerisation assays suggested that compound I 20 promoted protofilament assembly. In support of this possibility, computational docking studies revealed a strong interaction between compound I 20 and tubulin Arg β369, which is also the binding site for the anticancer drug Taxol. Our results suggest that (Z)-2-(5-benzylidene-4-oxo-2-thioxothiazolidin-3-yl)-N-phenylacetamide derivatives could have utility for the development of microtubule-stabilising therapeutic agents.